Market links between actors of the Honduran coffee supply chain: Challenges and opportunities - Ceballos-Sierra, Federico (International Food Policy Research Institute, 2022)
Coffee is one of the major crops produced in Honduras. This country is the world’s sixth largest producer and the largest producer in Central America. Its contribution to the economy cannot be overstated: it accounts for 5% of the national Gross Domestic Product (GDP) and 26% of the agricultural GDP. It is also the second most important source of foreign currency after international money transfers, bringing 1.165 million USD in the 2020/2021 harvest (IHCAFE 2021). Currently, up to 120,000 Honduran farmers produce coffee, 95% of which are smallholder farmers that produce less than 5000 pounds of coffee yearly (Christian Bunn et al. 2018). The sector employs an estimated 1,1 million people directly. Many more depend on it indirectly (Mogrovejo 2020). Its production is geographically dispersed, being grown in 15 of the 18 departments and in 221 of the 298 municipalities (IHCAFE 2021).